(untitled) (Orthodontic Journal of Nepal, 2021)
Missing maxillary lateral incisor is the most prevalent developmental dental anomaly. The management of missing lateral incisor, either need to be closed and use canine as substitution or create space orthodontically for the prosthetic replacement of the missing lateral incisors. A careful diagnosis and treatment plan are deemed essential to address the patient’s needs as the spacing is present in the esthetic region of the jaw which is very challenging so it should be managed by multidisciplinary approach including specialists in orthodontics, prosthodontics, operative dentistry and periodontist. Space closure with canine lateralization option seems less invasive, treatment can be completed relatively in short period of time and it’s adaptation with the facial changes throughout life without having artificial prosthesis provided other factors favoring for this option. This review article describes the various treatment options and their ideal indications, contraindications, advantages and disadvantages as well as emphasize on some modifications in the treatment mechanics which is crucial to achieve the optimal esthetic and to improve the occlusion.